Anti-coreceptor antibodies profoundly affect staining with peptide-MHC class I and class II tetramers. - Wooldridge, L; Scriba, T; Milicic, A; Laugel, B; Gostick, E; Price, D; Phillips, R; Sewell, A (2006)
The T cell coreceptors CD8 and CD4 bind to invariable regions of peptide-MHC class I (pMHCI) and class II (pMHCII) molecules, respectively, and facilitate antigen recognition by a number of mechanisms. It is established that some antibodies (Ab) specific for the CD8 molecule, which stabilizes TCR/pMHCI interactions, can alter the binding of pMHCI tetramers to cell surface TCR. In contrast, the extremely weak pMHCII/CD4 interaction does not stabilize TCR/pMHCII interactions or contribute to cognate tetramer binding; consequently, it is assumed that anti-CD4 Ab do not affect pMHCII binding. Here, we used a panel of point-mutated HLA A2 molecules with a range of affinities for CD8 spanning over three orders of magnitude to demonstrate that anti-CD8 Ab-mediated inhibition of pMHCI tetramer binding and cognate T cell activation correlates directly with the strength of the pMHCI/CD8 interaction. Further, some anti-CD4 Ab were found to block pMHCII tetramer binding; these effects were also paralleled in T cell activation assays. In sum, these data challenge the assertion that anti-coreceptor Ab exert their effects on T cell activation and pMHC binding solely by blocking pMHC/coreceptor interactions.